Relevance of plant growth-promoting bacteria in reducing the severity of tomato wilt caused by Fusarium oxysporum f. sp. lycopersici by altering metabolites and related genes - Ansari, Waquar Akhter; Krishna, Ram; Kashyap, Sarvesh Pratap; Al-Anazi, Khalid Mashay; Abul Farah, Mohammad; Jaiswal, Durgesh Kumar; Yadav, Akhilesh; Zeyad, Mohammad Tarique; Verma, Jay Prakash (Frontiers in Microbiology, 2025)
Among the biotic stresses, wilt disease severely affects tomato quality and productivity globally. The causal organism of this disease is Fusarium oxysporum f. sp. lycopersici (Fol), which is very well known and has a significant impact on the productivity of other crops as well. Efforts have been made to investigate the effect of plant growth-promoting bacteria (PGPB) on alleviating tomato wilt disease. Four PGPB strains, such as Pseudomonas aeruginosa BHUPSB01 (T1), Pseudomonas putida BHUPSB04 (T2), Paenibacillus polymyxa BHUPSB16 (T3), and Bacillus cereus IESDJP-V4 (T4), were used as inocula to treat Fol-challenged plants. The results revealed that PGPB treatments T1, T2, T3, and T4 were able to decrease the severity of Fusarium wilt in the tomato plants at different levels. Among the treatments, T3 displayed the strongest protective effect, with the lowest disease frequency, which was 15.25%. There were no significant differences observed in parameters such as fruit yield and relative water content in the PGPB-inoculated plants, although T3 and T4 showed minimal electrolyte leakage. Significant changes in chlorophyll fluorescence were also recorded. A lower level of H2O2 and malondialdehyde (MDA) was observed in the T3 and T4 treatments. In addition, proline accumulation was highest in the T3-treated plants. Antioxidative enzyme activities, such as catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD), significantly increased in the PGPB-treated plants. Furthermore, the highest phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO) activity was reported in the T3 and T4 plants, respectively. The PGPB-treated plants showed elevated expression of the PAL, PPO, PR3, PR2, SOD, CAT, and PO genes. This study’s results reveal that PGPB strains can be utilized as biocontrol agents (BCAs) to enhance tomato resistance against Fusarium wilt.